(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Ethnicity plays a significant role in shaping social structures, opportunities, and individual experiences. It influences access to education, healthcare, employment, and political representation, often intersecting with socioeconomic status, discrimination, and cultural identity.